2018
DOI: 10.1556/030.65.2018.044
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of blaVEB and blaGES among VIM-producing Pseudomonas aeruginosa clinical isolates in Alexandria, Egypt

Abstract: Thirty-three Pseudomonas aeruginosa isolates, resistant to one or more β-lactams, were included in this study. Identification of tested strains was confirmed using MALDI-TOF/MS. Phenotypic and genotypic β-lactamase patterns were investigated. Most of the isolates were resistant to carbapenems (32 out of 33) and to the extended-spectrum cephalosporins (ESC) (30 out of 33). Phenotypically, the production of extended-spectrum beta-lactamase (ESBL), metallo-β-lactamases (MBL), and carbapenemases was detected in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…It is reasonable to explain that this may be correlated with the extent use of carbapenems in recent years as well as a selective pressure from increased prescriptions of carbapenem. As anticipated, similar high rates of resistance have been recorded in Egypt (Gaballah et al 2018;Abaza et al 2017). The frequency of carbapenem resistance P. aeruginosa was also recognized in our Middle East (Castanheira et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…It is reasonable to explain that this may be correlated with the extent use of carbapenems in recent years as well as a selective pressure from increased prescriptions of carbapenem. As anticipated, similar high rates of resistance have been recorded in Egypt (Gaballah et al 2018;Abaza et al 2017). The frequency of carbapenem resistance P. aeruginosa was also recognized in our Middle East (Castanheira et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…35 However, our results show a dominance of blaVIM-1, which is not in agreement with earlier studies carried out in Egypt showing a dissemination of bla-VIM-2 instead or the universal bla-VIM genes. 34,36 Interestingly, we report here for the first time in Upper Egypt the emergence of New Delhi metallo-beta-lactamase −1 gene (bla-NDM) harboring isolates, which possessed bla-VIM-1 as well and showed high-level resistance. There are no previous reports of bla-NDM in Egypt, except a case report of two isolates recovered from a tertiary hospital in 2012.…”
Section: Discussionmentioning
confidence: 86%
“…The results shown in Table 1 indicate that in Egypt from 2000 through 2020, resistance to various cephalosporins, such as cefuroxime, cefotaxime, ceftazidime, and cefepime, was higher than that to b-lactam/b-lactamase inhibitor combinations, e.g., amoxicillin-clavulanic acid and piperacillin-tazobactam. A rise in resistance was reported against aminoglycosides; gentamcin/amikacin, ciprofloxacin (a quinolone drug) and carbapenems, i.e., imipenem and meropenem [ 84 , 85 , 86 , 87 , 88 , 89 ]. The increase in antibiotic resistance in these isolates has also been demonstrated by β-lactamase detection.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in antibiotic resistance in these isolates has also been demonstrated by β-lactamase detection. These studies from Egypt reported the phenotypic prevalence of ESBLs in E. coli and ESKAPE pathogens with ESBL rate of 7.4%, which increased to 48.9% [ 84 , 89 , 90 , 91 , 92 ]. Molecular characterization of the ESBL trait with PCR showed that bla SHV , bla TEM and bla CTX-M were the most predominant traits among E. coli and ESKAPE pathogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation